Experimental analysis of the flow around ahmed bodies in tandem position - Martins, Gustavo Xavier [UNESP]; Aranda, Gabriel dos Santos; Campos, Henrique Matos; Pantaleão, Aluisio Viais [UNESP] (ABCM, 2022)
Use of experimental methods is fundamental for the automobile industry, as it allows one to analyze aerodynamic phenomena that are crucial for the development of automobiles. A coherent method is to use Ahmed bodies with different rear inclination angles as a reference model, considering that it has been used in studies that aim to analyze the flow of land vehicles, whilst generating satisfactory results. So, in this experimental work, we explored the impact of the rear inclination angle and the spacing between Ahmed bodies in tandem (simulating a truck convoy), aiming to determine the best configuration concerning the drag reduction. The experimental methodology used flow visualization techniques in the horizontal hydrodynamic tunnel. The flow was visualized and registered by a camera for different rear inclination angles (10°, 20°, 30° and 35°) and different gap ratios (0.5 to 1.0) between the Ahmed bodies at a fixed Reynolds number of 2:06 103. Thus, we observed that, even if differences in the flow were presented in all cases, the body with a rear slant angle of 30° has the biggest wake region not mattering the spacing between models. Additionally, the impact of the gap ratio varied for each rear inclination angle.
Keywords: Automobile industry; Experimental analysis; Flow visualization; Horizontal hydrodynamic tunnel; Ahmed body